The effect of pilis therapy on reducing headaches (Chepalgia) in postpartum mothers at the Niar clinic, Timbang Deli regency, Medan Amplas district in 2023 - Kristina, Kristina; Fadillah, Fitriani (Jurnal EduHealth, 2024)
Headaches that occur in postpartum mothers can have a negative impact on the baby if not addressed, namely reducing the quality of life, reducing the ability to do activities and reducing the ability to care for the baby. Management of headaches in postpartum mothers can be overcome pharmacologically and non- pharmacologically. Non-pharmacological treatment includes traditional medicine, namely the use of pilis therapy applied to the forehead of puerperal mothers. The purpose of this study was to analyze the effect of pilis therapy on reducing headache (Chepalgia) in puerperal mothers. This type of research is quantitative research using Experimental Research with a Pre-experimental research design using a one group pretest posttest only design design. The population in this study was all postpartum mothers who gave birth at the Niar Clinic, Timbang Deli Regency, Medan Amplas District. The sampling technique in this study used accidental sampling by meeting the inquisition criteria of 20 people. The data collection method uses observation sheets. The statistical test used in this study is the Wilcoxon Rank Test. The results of this study are known to have differences before and after pilis therapy in postpartum mothers. The results of the Wilcoxon Rank Test analysis obtained a p-value of 0.00 < 0.05 which means that there is an effect of pilis therapy on reducing headaches (Chepalgia) in postpartum mothers at the Niar Clinic, Timbang Deli Regency, Medan Amplas District. The conclusion of this study shows that there is an effect of pilis therapy on reducing headaches (Chepalgia) in postpartum mothers at the Niar Clinic, Timbang Deli Regency, Medan Amplas District. So it is expected that the community will continue to apply pilis therapy regularly after giving birth to postpartum mothers who experience headaches (Chepalgia).